PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF “SIBANGTAR (NUMERASI KELILING BANGUN DATAR)’’ PADA SISWA KELAS V SD - Nova Oktavia Sari; Dra. Dian Kusmaharti, S.Si., M. Pd (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Interactive learning media is a learning media designed to actively involve students in the learning process. This study aims to develop interactive learning media on the material of the circumference of flat shapes in grade V of elementary school. This study uses the ADDIE research model with several stages including Analysis, Design, Development, Implementation, Evaluation. This study created an interactive learning media based on android with an assessment from three validators, namely material experts with a value of 94%, media experts with a value of 90%, and language experts with a value of 90% all meeting the criteria of "very feasible". The results of the student response assessment using 1 trial, namely a small group trial, the value of the media presentation obtained a value of 91% all meeting the criteria of "very feasible". So this shows that the development of this SIBANGTAR interactive learning media is feasible to be implemented in learning.